2000
DOI: 10.1200/jco.2000.18.22.3758
|View full text |Cite
|
Sign up to set email alerts
|

Anastrozole Is Superior to Tamoxifen as First-Line Therapy for Advanced Breast Cancer in Postmenopausal Women: Results of a North American Multicenter Randomized Trial

Abstract: Anastrozole satisfied the predefined criteria for equivalence to tamoxifen. Furthermore, we observed both a significant increase in TTP and a lower incidence of thromboembolic events and vaginal bleeding with anastrozole. These findings indicate that anastrozole should be considered as first-line therapy for postmenopausal women with advanced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
406
2
27

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 919 publications
(449 citation statements)
references
References 35 publications
14
406
2
27
Order By: Relevance
“…The HR for PFS seen in this 321 study (0·797) is similar to the improvement shown by third-generation AIs over Page 16 tamoxifen. [4][5][6][7][8] In addition to the primary endpoint results, pre-defined subgroup 323 analyses were performed. The test for heterogeneity was not statistically significant 324 across all the subgroups although it was noted that potential enhanced treatment 325 effects with fulvestrant vs anastrozole were seen in some subgroups, including 326 patients with non-visceral disease compared with visceral disease.…”
Section: Page 15mentioning
confidence: 99%
“…The HR for PFS seen in this 321 study (0·797) is similar to the improvement shown by third-generation AIs over Page 16 tamoxifen. [4][5][6][7][8] In addition to the primary endpoint results, pre-defined subgroup 323 analyses were performed. The test for heterogeneity was not statistically significant 324 across all the subgroups although it was noted that potential enhanced treatment 325 effects with fulvestrant vs anastrozole were seen in some subgroups, including 326 patients with non-visceral disease compared with visceral disease.…”
Section: Page 15mentioning
confidence: 99%
“…The median overall survival for the patients relapsing at our institution (40.7 months), was higher than the 10-20 months Months since relapse Proportion of patients surviving reported with first-line metastatic studies in the UK and Europe evaluating metastatic chemotherapy regimens [18,19], but it was fairly comparable with the 20-30 months reported within first-line metastatic aromatase versus tamoxifen studies [9,20]. Although the median figure of £31,403 (Table 4) for treating a relapse is higher than previous UK estimates, the data is more recent and included the 30% of the community cost not previously collected.…”
Section: Discussionmentioning
confidence: 62%
“…As such, even the presence of estrogenic endocrine-active compounds would likely not be able to bypass the effects of tamoxifen [54]. However, due to the side effects (increased osteoporosis and incidence of uterine cancer) of tamoxifen use, there is a push to utilize other treatment strategies, such as aromatase inhibitors [55][56][57]. Aromatase inhibitors block the metabolism and formation of estrogen, thereby reducing the estrogenic signaling capacity or ER, however, leaving the ER intact and fully functional.…”
Section: Are Other Environmental Contaminants Inferring With Disease mentioning
confidence: 99%